Youth and adult education in the municipality of Marilia in the period 2009-2019 - Goncalves, Talita dos Santos [UNESP]; Padua Sabia, Claudia Pereira de [UNESP] (Univ Federal Sergipe, 2021)
The Youth and Adult Education (YAE) modality was established by the Law of Guidelines and Bases for National Education (LDBEN) in 1996. YAE is intended for people over 18 years of age who have not completed elementary and secondary education and this type of education it is the opportunity for them to continue or start schooling. The objective of the study was to identify how the offer of this modality is organized in the city of Marilia between 2009-2019 and to verify its characteristics, its possible advances and/or setbacks. The research had a Scientific Initiation grant from the Foundation for Research Support of the State of Sao Paulo (FAPESP). The methodology uses a qualitative approach and bibliographic and documentary research. The documentary research consisted of the National Education Plan (PNE 2014-2024) and the Municipal Education Plan (PME 2015-2025) and the Statistical Synopsis of the National Institute of Educational Studies and Research Anisio Teixeira (INEP). As a result, we identified a mismatch between the goals established in the PME (2015-2025) and the enrollments carried out in the YAE in the studied municipality, which have been decreasing sharply between 2009-2019. We also verified in the PPP of two surveyed schools, which both bring in their Teaching Plan for YAE, repetitive content and a language aimed at children, constituting an inadequate methodology for the target audience, mostly composed of adults and elderly people above 60 years old, disregarding the life context of its students, their trajectories and experiences, contrary to what Paulo Freire proposes in his method and adult literacy for reading the word and reading the world.
Keywords: Illiteracy; Municipal Education Plan of Marilia; National Education Plan; Public Policies for Youth and Adult Education (YAE); Right to education